(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This study is aimed at determining the composition of phytonematodes and their ecological groups found in onion (Allium cepa) crops grown in the Darkhan district of the Akdarya district of the Samarkand region. Soil samples were taken from a depth of 15–30 cm and analyzed using route, funnel (Baermann), and incubation methods. As a result of the study, more than 300 nematodes were identified, which were divided into ecological groups such as polytrofes, eusaprobionts, devisaprobionts, and phytohelminths. The most common species are Panagrolaimus rigidus and Aphelenchus avenae, which play an important role in the agro-ecosystem. The research results are of great importance for monitoring nematodes in onion crops and developing control measures against them.